ChemInform Abstract: Review on Nanomaterials Synthesized by Vapor Transport Method: Growth and Their Related Applications. Issue 45 (November 2015) - Xue, X.; Zhou, Z.; Peng, B.; Zhu, M. M.; Zhang, Y. J.; Ren, W.; Ye, Z. G.; Chen, X.; Liu, M.
Abstract Review: 88 refs.